Accelerated corrosion of pipeline steel under dynamic DC stray current interference. (16th November 2020) - Qin, Huimin; Du, Yanxia; Lu, Minxu; Liu, Jie; Zhu, Xiangjian
ABSTRACT: In this paper, the statistical analysis of fluctuation characteristics of pipeline potential under dynamic DC stray current interference was carried out based on field test data. Then a self-designed experimental set-up was applied to study the corrosion behaviour of X70 steel in soil-simulating conditions. The statistical results showed that under the dynamic DC stray current interference, the pipeline potential was periodically fluctuated with dynamic periods between 10 and 300 s. The laboratory experiment results showed that there was a strong correlation between the corrosion rate and the dynamic period. When the dynamic period was less than 300 s, the corrosion rate was less than 22% of the predicted corrosion rate via Faraday's law. Then corrosion mechanism was discussed based on a series of experimental measurment results. The interface capacitance effect, as well as the charge consumption by extra reaction, acted a significant part in depressing metal dissolution under dynamic DC stray current interference.